Toward a Unification of the Arts - Brown, Steven (Frontiers in Psychology, 2018)
This article presents a manifesto for the scientific exploration of the arts in their totality, rather than conceiving of each artform independently on its own terms. In order to achieve this, I present an analytical procedure that is comprised of two related steps. The first step is to identify instances of sharing in the production mechanisms across artforms, for example the occurrence of rhythmic structure in music, dance, and poetry. The second is to examine how this sharing creates “affordances for combinations”, making it possible for music to be set to a poem or for dance movements to be choreographed to music. By elucidating the neurocognitive mechanisms of sharing across arts domains and the affordances that they offer for creating combinations, it should be possible to achieve a unification of the arts.